Clinical and molecular characterization of familial chylomicronemia in Saudi patients: a retrospective study - Al-Ashwal, Abdullah; AlHelal, Manal; AlSagheir, Afaf; Alfattani, Areej; Ramzan, Khushnooda; Imtiaz, Faiqa; Alhuthil, Raghad (Frontiers in Endocrinology, 2024)
Introduction Familial chylomicronemia syndrome (FCS) is a severe type of hypertriglyceridemia (HTG). Despite its rarity, we have encountered more than 100 patients with FCS at our center. Therefore, we aimed to provide a useful resource for clinicians who may encounter such patients and help the scientific community accumulate knowledge to manage this disease. Methods This retrospective study described the clinical characteristics and management of FCS patients at (King Faisal Specialist Hospital and Research Centre, Riyadh, Saudi Arabia). Results In total, 29 pediatric patients were included, with a median age of 2.2 months [IQR: 1.3, 12]. Males predominated (62.0%). Key symptoms included a milky blood sample (72.4%), a family history of HTG (65.5%), hepatosplenomegaly (44.8%), acute pancreatitis (31.0%), and eruptive xanthoma (13.8%). Gemfibrozil (22 patients) reduced TG from 47.6 ± 55.7 to 9.4 ± 7.5 mmol/L (mean reduction 38.2 ± 54.5 mmol/L, P<0.001). Fenofibrate (19 patients) lowered TG from 45.4 ± 56.4 to 18.4 ± 13.1 mmol/L (mean difference 27.1 ± 52.0 mmol/L, P=0.001). While the Niacin-aspirin (4 patients) and diet alone (4 patients) had no significant effect (P=1.000) and (P=0.125), respectively. Discussion The rarity of FCS makes it more challenging for scientists and clinicians to achieve advancements in its management. We observed that anti-TG medications, especially fibrate derivatives, can be used safely in pediatric patients. They displayed excellent ability to control TG levels in combination with diet restrictions, and treatment compliance was good. Among fibrate derivatives, gemfibrozil controlled TG levels better than fenofibrate, and neither drug had significant side effects.